Stated product formulation preferences for HIV pre-exposure prophylaxis among women in the VOICE-D (MTN-003D) study - Luecke, Ellen H (J Int AIDS Soc, 2016)
INTRODUCTION: The effectiveness of HIV pre-exposure prophylaxis (PrEP) requires consistent and correct product use, thus a deeper understanding of women's stated product formulation preferences, and the correlates of those preferences, can help guide future research. VOICE-D (MTN-003D), a qualitative ancillary study conducted after the VOICE trial, retrospectively explored participants’ tablet and gel use, as well as their preferences for other potential PrEP product formulations. METHODS: We conducted an analysis of quantitative and qualitative data from VOICE-D participants. During in-depth interviews, women were presented with pictures and descriptions of eight potential PrEP product formulations, including the oral tablet and vaginal gel tested in VOICE, and asked to discuss which product formulations they would prefer to use and why. Seven of the original product formulations displayed were combined into preferred product formulation categories based on exploratory factor and latent class analyses. We examined demographic and behavioural correlates of these preferred product formulation categories. In-depth interviews with participants were conducted, coded, and analysed for themes related to product preference. RESULTS: Of the 68 female participants who completed in-depth interviews (22 South Africa, 24 Zimbabwe, 22 Uganda), median age was 28 (range 21–41), 81% were HIV negative, and 49% were married or living with a partner. Four preferred product formulation categories were identified via exploratory factor analysis: 1) oral tablets; 2) vaginal gel; 3) injectable, implant, or vaginal ring; and 4) vaginal film or suppository. A majority of women (81%) expressed a preference for product formulations included in category 3. Characteristics significantly associated with each preferred product category differed. Attributes described by participants as being important in a preferred product formulation included duration of activity, ease of use, route of administration, clinic- versus self-administration, and degree of familiarity with product. CONCLUSIONS: While there was interest in a variety of potential PrEP product formulations, a majority of VOICE-D participants preferred long-acting methods. More research is needed to gain insight into end-users’ product formulation preference to inform messaging and market segmentation for different PrEP products and resources to invest in products that target populations are most interested in using. Clinical Trial Number: NCT02358616